2018
DOI: 10.1186/s13054-018-2251-2
|View full text |Cite
|
Sign up to set email alerts
|

Is goal-directed fluid therapy based on dynamic variables alone sufficient to improve clinical outcomes among patients undergoing surgery? A meta-analysis

Abstract: BackgroundWhether goal-directed fluid therapy based on dynamic predictors of fluid responsiveness (GDFTdyn) alone improves clinical outcomes in comparison with standard fluid therapy among patients undergoing surgery remains unclear.MethodsPubMed, EMBASE, the Cochrane Library and ClinicalTrials.gov were searched for relevant studies. Studies comparing the effects of GDFTdyn with that of standard fluid therapy on clinical outcomes among adult patients undergoing surgery were considered eligible. Two analyses we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 52 publications
0
39
0
Order By: Relevance
“…Static preload indices such as central venous pressure are not su cient to assess uid responsiveness (2) whereas dynamic preload indices such as pulse pressure variation (PPV) and stroke volume (SV) variation have been used successfully. (3) However, such indices suffer from several limitations and should be used only under strict conditions. (4) Alternative dynamic methods of assessment such as lung recruitment maneuvers (LRM) have been developed.…”
Section: Introductionmentioning
confidence: 99%
“…Static preload indices such as central venous pressure are not su cient to assess uid responsiveness (2) whereas dynamic preload indices such as pulse pressure variation (PPV) and stroke volume (SV) variation have been used successfully. (3) However, such indices suffer from several limitations and should be used only under strict conditions. (4) Alternative dynamic methods of assessment such as lung recruitment maneuvers (LRM) have been developed.…”
Section: Introductionmentioning
confidence: 99%
“…There is quite strong evidence to support the benefits of GDFT in high-risk patients undergoing major surgical procedures [ 9 , 11 ]. Indeed, over the past 15 years, several meta-analyses of the impact of GDFT in patients undergoing moderate and high-risk surgeries have observed that GDFT improves outcome compared with routine care [ 8 , 11 , 17 20 ]. However, the studies included in these meta-analyses are highly heterogeneous, with different protocols, different physiologic endpoints, and different technologies to measure stroke volume and cardiac output.…”
Section: Main Textmentioning
confidence: 99%
“…Thus, compared with open abdominal surgery, the risk of respiratory failure, ARDS, pulmonary infections, and pulmonary embolism can be reduced by applying a laparoscopic approach [94]. Perioperative fluid therapy and transfusion can also trigger postoperative ARDS; therefore, a restrictive goal-directed fluid strategy should be considered for patients with high risk of PPC [95,96]. Volatile anesthetics have lung-protective potential and can improve the surgical outcome as well [97].…”
Section: Protective Ventilation During Perioperative Periodmentioning
confidence: 99%